The Effect of Teaching With The Differentiated Education Strategy On The Achievement of Physics And The Development Of Reflective Thinking Among Third Grade Intermediate Students - Abdal, Hassan Arif (Indonesian Journal of Humanities and Social Sciences, 2023)
The study aimed to learn the impact of teaching with differentiated education strategy in physics acquisition and meditative thinking development among third- grade middle students. The researcher selected the Mediocre Boys in Baghdad as an intentional sample of the experiment, and the research sample reached (58) Students in the third grade average (29) students for each of the two research groups rewarded the researcher between the two research groups in time-age variables with months, intelligence, previous information and a measure of contemplative thinking, The researcher prepared a multi-choice collection test and applied it to the two research groups and adopted a special measure of meditative thinking, after ascertaining its sincerity and consistency, the researcher used the T- test (T-test) to learn the results, and found that the differentiated education strategy had an effective impact on physics attainment and meditative thinking development for the experimental group compared with the control group. The researcher suggested a number of recommendations and proposals.